Treatment strategies for neuroendocrine liver metastases: a systematic review. Issue 11 (November 2022) - Muttillo, Edoardo M.; Mazzarella, Gennaro; Picardi, Biagio; Rossi, Stefano; Cinelli, Lorenzo; Diana, Michele; Baiocchini, Andrea; Felli, Eric; Pessaux, Patrick; Felli, Emanuele; Muttillo, Irnerio A.
Abstract: Background: Gastroenteropancreatic neuroendocrine tumors are often diagnosed when metastatic. The liver is the main site of metastases. Unfortunately, optimal management of neuroendocrine liver metastases remains a topic of debate. The aim of this study was to make a systematic review of the current literature about the results of the different treatments of neuroendocrine liver metastases. Methods: A systematic review was conducted for English language publications from 1995 to 2021. Outcomes were analyzed according to survival, disease-free survival, and in the case of systemic therapies, progression-free survival. Results: 5509 patients were analyzed in the review. 67% of patients underwent surgery achieving 5 years overall survival despite only 30% percent without a recurrence. 60% of patients that had received a transplant reached 5 years survival with a low disease-free survival rate (20%). Five-year survival rate was 36.2% for patients undergoing loco-regional therapies. Conclusion: Surgical resection is the best treatment when metastases are resectable, with the highest rate of survival, although liver transplantation shows good results for patients not eligible for surgery. Loco-regional therapies may be useful when surgical resection is contraindicated, or selectively used as a bridge to surgery or transplantation. Systemic therapies are indicated in patients for whom curative treatment cannot be obtained.